Portugal : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2016)
This Selected Issues paper estimates the fiscal impact of demographic changes in Portugal and the euro area over the period 2015-2100. Under the baseline projections of the United Nations, Portugal is among the countries in the euro area that is expected to be most hurt by demographic developments. During 2015-2100, its population is expected to shrink by about 30 percent while the old-age dependency ratio is expected to more than double, driven mostly by low fertility, higher longevity, and migration outflows. Age-related public spending would increase by about 6 percentage points of GDP under the baseline over the period 2015-50, and the public debt path would become unsustainable in the absence of offsetting policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet